Implementasi Projek Penguatan Profil Pelajar Pancasila di PAUD Al-Azhar Pagendingan Kecamatan Galis Kabupaten Pamekasan - Lily Nur Indah Sari; Navlia, Rusdiana; Nisa’, Miladia Khoirun (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aims to examine the implementation of the Pancasila Student Profile Strengthening Project which was carried out at PAUD Al-Azhar Pagendingan, Galis District, Pamekasan Regency with two main focuses. First, regarding the Implementation of the Pancasila Student Profile Strengthening Project Activities, and second, How to Build Early Childhood Ideals through Pancasila Student Profile Strengthening Project Activities. This study uses a qualitative research method with a descriptive type of research. The data collection techniques used in this study use interview, observation and documentation techniques. Data analysis using. data reduction, data presentation, and conclusion drawn. Data validation using triangulation. Building children's ideals can be done through a series of activities of the Pancasila Student Profile Strengthening Project (P5) which means, among others, carrying out the initial stage, development stage and the preliminary stage. The implementation of Strengthening the Pancasila Student Profile encourages children to have the desire and enthusiasm to learn in order to build ideals and understand the importance of the profession as a form of contributing to nation building, which ultimately strengthens the dimension of Pancasila character and national values through an active, meaningful, collaborative and fun learning environment.